Assessment of senior pupils’ physical fitness considering physical condition indicators - I.R. Bodnar; M.V. Stefanyshyn; Y.V. Petryshyn (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2016)
Consideration of physical condition indicators in assessment pupils’ physical fitness permits to differentiate training and health restoration processes at physical culture lessons. Purpose: to substantiate criteria for pupils’ physical fitness assessment, considering their physical condition indicators. Material: in the research 10-11 form pupils (n=406; 211boys and 195 girls) participated. After physical fitness testing by requirement of acting programs we carried out diagnostic of pupils’ psycho-emotional state. Results: by results of physical; fitness we observed substantial deviation from universal law of normal distribution. It was found that physical condition indicators of most pupils are beyond normal. It was also determined that the most informative indicators are body length, chest circumference and body relative mass. We substantiated that it is necessary to consider physical condition indicators, when determining physical fitness level. We also substantiated and worked out differentiated normative for assessment pupils’ physical fitness. Conclusions: testing without consideration physical condition indicators does not facilitate pupils’ motivation for further physical self-perfection. Such testing results in high situational anxiety and unfavorable psycho-emotional state of pupils.